Leadership as a determinant of need fulfillment: implications for meta-theory, methods, and practice - Pincus, J. David (Frontiers in Psychology, 2024)
Of all the most prominent business concepts (e.g., DE&I, employee well-being, employee engagement, organizational culture, etc.) none rivals leadership in terms of public interest and annual monetary investment. Despite the obvious importance of leadership as a determinant of many important outcomes, the concept of leadership has been surprisingly hard to pin down, lacking consensus as to its precise meaning. As numerous authors introduce ever more constructs (e.g., servant leadership, toxic leadership, sustainable leadership, transformational leadership, etc.), the leadership concept has become emblematic of the problem of construct proliferation.Like the related fields of employee engagement, subjective well-being, and organizational culture, the leadership field is in desperate need of a clearly articulated meta-theory to house its many constructs, allowing theory and measurement to build up instead of continuing to pile up. This paper argues for grounding the concept of leadership within the psychological literature on human needs. In reviewing the leading definitions of leadership in the literature we find that they are reducible to a core set of follower needs that can be facilitated or inhibited by leaders. We propose that there is substantial value in adopting a comprehensive needs-based taxonomy over current approaches. We consider the impact of setting the concepts of leadership within existing need constructs for each of the following: (a) theory, especially the development of leadership frameworks and particularly how the concept of leadership relates to the concepts of organizational culture, employee well-being, and employee engagement; (b) methods, including the value of applying a comprehensive, structured model; and (c) practice, where we emphasize the practical advantages of clear operational definitions.